Can the Gram-negative bacterium Escherichia coli colonize the gut of Lone Star Tick (Amblyomma americanum)? - McKenzie, Taylor; Vanderree, Tessa; Maldonado-Ruiz, Paulina; Park, Yoonseong; Zurek, Ludek (My University, 2018)
Ticks are obligate blood feeding ectoparasites and vectors of several mammalian pathogens (Williams-Newkirk et al, 2014). In addition to pathogens they also carry a bacterial community with commensal and symbiotic relationships (Bonnet et al, 2017). Using a culture-dependent approach we previously reported a high prevalence of Gram-positive bacteria in the gut of field collected lone star ticks (Amblyomma americanum). These results suggested that epithelial immunity functions to control Gram-negative bacteria in A. americanum. In this study, we used a culturing and non-culturing approach to measure the outcome of E.coli (Gram-negative) when fed to female adult lone star ticks (n=16). Results showed a significant reduction of E.coli at Days 1, 3 and 7 post bacterial feeding. qPCR of 16S rDNA confirmed reduction of bacterial rDNA when compared to water fed ticks (n=16). Our results suggest that there is a midgut epithelial immune response in place, which mainly targets Gram-negative bacteria!
Keywords: Fall 2018